Comparison of Institutional Aspects in Handling COVID-19 in Taiwan and Indonesia - Heryati, Neneng (Journal of Governance and Administrative Reform, 2023)
Abstract World Health Organization(WHO) declared COVID-19 a global pandemic. It is important to consider government policies in handling COVID-19. Taiwan is a country that has succeeded in implementing policies to address COVID-19. Meanwhile, Indonesia still has to struggle in dealing with COVID-19, which until now is still increasing. Comparison between Taiwan and Indonesia in handling COVID-19 in institutional relations has similarities and differences. The policies taken by the governments of Taiwan and Indonesia are similar from an institutional perspective, namely by jointly forming a task team that involves several institutions and resources. While the difference is that in Taiwan, the command and coordination of inter-agency relations for handling the COVID-19 outbreak are under the control of the Minister of Health and Welfare. In contrast, in Indonesia, the Task Force for the Acceleration of Handling COVID-19 is led by the Head of the National Disaster Management Agency (BNPB). There is still an asymmetry in authority, institutional relations, and regulations in handling the COVID outbreak in Indonesia, so new rules and disaster management institutions are needed. Keywords: COVID-19, policy, institution, comparison, regulation     Abstrak   World Health Organization (WHO) menetapkan COVID-19 sebagai pandemik global.  Penting untuk mempertimbangkan kebijakan pemerintah dalam penanganan COVID-19. Taiwan termasuk negara yang berhasil dalam menerapkan kebijakan dalam penanganan COVID-19. Sedangkan Indonesia masih harus berjuang dalam menangani COVID-19 yang hingga saat ini yang masih meningkat. Perbandingan antara Taiwan dan Indonesia dalam penanganan COVID-19 dalam aspek hubungan kelembagaan ada persamaan dan perbedaan. Persamaan kebijakan yang diambil pemerintah Taiwan dan Indonesia dari sisi kelembagaan, yaitu dengan sama-sama membentuk tim tugas yang melibatkan beberapa lembaga dan sumberdaya di dalamnya. Sedangkan perbedaannya di Taiwan komando dan koordinasi hubungan antar lembaga untuk penanganan wabah COVID-19 di bawah kendali Menteri Kesehatan dan Kesejahteraan sedangkan di Indonesia Gugus Tugas Percepatan Penanganan COVID-19 di pimpin oleh Kepala Badan Nasional Penanggulangan Bencana (BNPB). Masih adanya ketidaksinkronan kewenangan, hubungan kelembagaan dan regulasi dalam penanganan wabah COVID di Indonesia sehingga perlu regulasi baru dan penataan lembaga kebencanaan.   Kata kunci: COVID-19, kebijakan, kelembagaan, perbandingan, regulasi